Increasing BCI usability in the home: assessing the user and caregiver perspectives - Bruegger, Katie, author; Davies, Patti, advisor; Roll, Marla, advisor; Sample, Pat, committee member; Anderson, Chuck, committee member (Colorado State University. Libraries, 2017)
Objective. Despite research indicating that brain-computer interface (BCI) technology can be an effective option for persons with motor disabilities, BCI is currently not being used by this population on a regular basis. The purpose of this research is to determine the current usability of the BCI system in the user's home from the perspective of BCI users with motor disabilities and their caregivers in order to influence the future direction of BCI advancement to improve the usability of BCI technology for this population. Method. Within this study, there were four separate phases. In Phase 1, using feedback from five participants with motor disabilities and three caregivers for persons with motor disabilities, a questionnaire was developed for both BCI users and caregivers to assess the experience of setting up and using the BCI system. In Phase 2, these questionnaires were administered to five participants with motor disabilities and their caregivers a total of three times after experiencing the set-up and use of a P300 BCI system in the user's home on three separate occasions. In Phase 3, the responses of the questionnaires were analyzed and common themes and patterns were used to develop a list of questions to guide a focus group discussion. Finally, in Phase 4 a focus group consisting of three BCI users and two caregivers was held to gather more in depth information about the experience of using and setting up the BCI system. Throughout these phases, both quantitative and qualitative methods were used to analyze data. Results: Quantitative data analysis of questionnaire responses yielded no significant results; however, a variety of patterns were identified and within these patterns multiple patterns were found to approach significance. Relationships that approached significance included the difference between user and caregiver ratings for ease of use over time (z= -1.730, p= 0.084) and the difference between user and caregiver ratings for the likelihood of using or advocating for the use of BCI in the home on a regular basis (z= -1.792, p=0.073). These findings showed that ease of use decreased across the course of the three visits for both caregivers and users and that caregivers were more likely to advocate for the use of BCI on a regular basis than BCI users. When asked what area of life participants wanted this version and future versions of BCI to help increase users' current participation, the most common response chosen by users was environmental aids to daily living (EADL) while the most common response for caregivers was verbal and written communication. Qualitative analysis of the focus group provided answers to the three research questions (What are current barriers preventing BCI from being used by persons with disabilities on a regular basis in the home?; What are the aspects of BCI that BCI user's and caregivers enjoy?; And what are BCI users' and their caregivers' desires for the future of BCI) and yielded three emergent themes: the cost benefit analysis of BCI use, comparison of BCI to existing technology, and BCI and its relationship to independence. Conclusions. Although at its current state, none of the participants believed that the P300 BCI system would be a valuable addition to their life, users and caregivers agreed that in cases where the need was great enough, the challenges of using the system would be outweighed by its benefits. With the implementation of developments that decrease the challenges involved in setting up and using the system or the implementation of developments that increase the utility of real life applications, future BCI systems will become more practical options for a larger population.
Keywords: brain-computer interface; environmental control; assistive technology; occupational therapy; electronic aids to daily living